CAVEN: A Visual Novel-Based Educational Game for Learning Fundamental Web Programming Concepts in High School Education - Assyifa Azzahra Muthmainnah; Nuur Wachid Abdul Majid Majid (Journal of Educational Sciences, 2026)
Web programming is a fundamental competency in the digital era, yet high school students often struggle with its abstract, multi-layered concepts under conventional lecture-based instruction. This study develops and evaluates CAVEN (Chronicles of the Altered Virtual ENgine), a Ren'Py-based visual novel educational game introducing frontend, backend, and security concepts to high school students, developed using the Multimedia Development Life Cycle (MDLC) method across six stages: concept, design, material collecting, assembly, testing, and distribution. The game integrates interactive storytelling, quizzes aligned with Bloom's taxonomy, a scoring system, and multiple endings. Evaluation involved content and media expert validation, Black Box Testing across 20 scenarios, and the User Experience Questionnaire Short Version (UEQ-S) with 20 Grade 10 respondents. Expert validation yielded feasibility scores of 86.7% (media) and 76.7% (content); Black Box Testing yielded a perfect functionality score (X = 1.00); and UEQ-S results were strongly positive, with Pragmatic Quality (1.88), Hedonic Quality (1.98), and an Overall UX score of 1.93. These findings demonstrate CAVEN as an expert-validated, technically feasible medium delivering positive user experience, establishing usability and student engagement rather than direct learning effectiveness, thus offering teachers a supportive digital learning tool.